Perceptual learning in the comprehension of animation and animated diagrams - Lowe, Ric (Cambridge Press, 2015)
Animations are increasingly used to present complex information in technical and educational settings. Once reason for the rising popularity of these representations has been advancing technology that has greatly facilitated the authoring, presentation, and dissemination of animated displays. Another reason is the widespread assumption that animations are an intrinsically effective way of presenting information, especially subject matter in which dynamics play an important role. However, findings from recent research have cast doubt on the assumed universal effectiveness of animations. Much of this research has been conducted in the field of education, where there is a growing reliance on the use of animations in multimedia learning materials (Hoffler and Leutner, 2007). Too often, the effectiveness of animations as tools for explanation has fallen well short of educators' expectations. It is becoming clear that some of the shortcomings of explanatory animations originate in the perceptual challenges they can pose to learner processing. This chapter examines evidence for the importance of perception in the processing of animations with particular focus on the methodologies used to produce that evidence.